PEMBERDAYAAN MASYARAKAT DESA TUYAU MELALUI PROGRAM PENDIDIKAN KEAKSARAAN USAHA MANDIRI [THE EMPOWERMENT OF DESA TUYAU VILLAGERS THROUGH EDUCATION PROGRAM ON INDEPENDENT BUSINESS LITERACY] - Muhamad Affandi (Jurnal AKRAB, 2019)
Education cannot be separated from literacy. Even the conception is one of the benchmarks of the Human Development Index (HDI) conducted by UNDP. Today, the concept of literacy can not only be the ability of reading, writing and counting, but rather emphasize the functions of those skill in everyday life. One of the literacy education programs that becomes the focus of the government through the Directorate of Literacy and Equality Education Development is KUM. In its practice in the community, independent business literacy has been widely applied by various non-formal education units. Various non-formal education units have now been widely applied in Indonesia, both by the public, the private sector and individuals. The establishment of various non-formal education units is not only based on the philosophy of non-formal education, but more because of the needs felt by the community. The researcher is interested in doing an investigation related to the implementation of Independent Business Literacy in Tuyau Village with the aim of maintaining and developing literacy of students who have followed and / or achieved the basic literacy competencies through the introduction of the ability to independently work. In this study, the approach used was a qualitative approach with survey methods, through the stages of data reduction, data display and conclusion drawing. Referring to the learning process and the final assessment of independent business literacy conducted in Tuyau Village, East Barito Regency, it is known that students who were declared graduated and entitled to obtain SUKMA-L were 89 people. While the other students, 11 students, were declared not graduated for various reasons. As for the students who have not graduated (who has not reach the established competency standard yet), the treatment is still being given until now intensively and continuously.